The Diversity style guide - Kanigel, Rachele (Wiley-Blackwell, 2019)
"This guide attempts to help journalists, journalism students and other media writers prepare for those sometimes awkward conversations. We'll explore the subtle and not-so-subtle ways that words can alienate a source or infuriate a reader, how a thoughtless pun in a headline can elicit hundreds of angry letters or ignite a firestorm on social media. It also aims to give writers an understanding that diversity in journalism is first and foremost about accuracy, about representing an individual or a community or an issue fully and completely, about not leaving people out and about telling the whole truth"--